The role of SARS-CoV-2 nucleocapsid protein in antiviral immunity and vaccine development - Haiyun Yu; Fei Guan; Heather Miller; Jiahui Lei; Chaohong Liu (Emerging Microbes and Infections)
The coronavirus disease 2019 (COVID-19) has caused enormous health risks and global economic disruption. This disease is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The SARS-CoV-2 nucleocapsid protein is a structural protein involved in viral replication and assembly. There is accumulating evidence indicating that the nucleocapsid protein is multi-functional, playing a key role in the pathogenesis of COVID-19 and antiviral immunity against SARS-CoV-2. Here, we summarize its potential application in the prevention of COVID-19, which is based on its role in inflammation, cell death, antiviral innate immunity, and antiviral adaptive immunity.